Reconstructing Legal Responsibility for the Dissemination of False News Containing Discrimination to Achieve Justice - Abraham Kateyau; Eriyantouw Wahid; Endang Pandam (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2026)
Crimes within social media networks are highly susceptible to occur due to anonymity and ease of electronic communication. However, law enforcement against perpetrators of false news and discriminatory defamation in Indonesia faces significant legal uncertainty due to multiple interpretations of key provisions in the Electronic Information and Transactions (ITE) Law. This research addresses regulations on designating suspects who spread false news on social media, and the reconstruction of criminal liability for spreading hoaxes and discriminatory defamation through social media in Indonesia. Using a normative juridical method with comparative legal analysis which examining Indonesia’s ITE Law alongside Malaysia’s Communications and Multimedia Act 1998 and Singapore’s Protection from Harassment Act, the results indicate that reconstructing legal responsibility is necessary when false, discriminatory content, including SARA-based speech, spreads. This should be achieved through measured sanctions providing a deterrent effect to maintain societal order. Without this, law enforcement against such acts is undermined. However, implementing the ITE Law faces challenges, including multiple interpretations, human rights concerns, and digital evidentiary constraints. Therefore, it is recommended to revise legal norms for clarity and promote digital literacy education so the public can identify accurate information. Fair, proportional law enforcement is crucial to balance freedom of expression with protection from discrimination.